Diffusion in two-component quasiparticle systems of liquid and solid mixtures of helium isotopes - Adamenko, I.N.; Nemchenko, K.E.; Zhukov, A.V.; George, T.F.; Pandey, L.N.; Um, Chung-In (Condensed Matter Physics, 1999)
An exact expression for the diffusion time which depends on the interaction rates for particles of not only different, but also of the same species, has been derived from the system of kinetic equations. The result is valid for particles with arbitrary statistics and energy-momentum relations. The derived general relations are valid for investigating diffusion in liquid and solid ³He-⁴He mixtures. The contribution of interaction between quasiparticles of the same type to the diffusion coefﬁcient and effective thermal conductivity of superﬂuid solutions is analyzed. The calculated values are compared with experimental data. The calculated diffusion coefﬁcient of ³He-⁴He solid solutions differs from the previous theoretical results. A comparison of the obtained diffusion coefﬁcient with experimental data makes it possible to determine the numerical value of the energy band width for impurity quasiparticles.